COST PROFIT VOLUME ANALYSIS OF BIG CHILI FARMING IN JEMBER REGENCY - Muhammad Firdaus; Suherman Suherman; Farid Wahyudi; Ahmad Sauqi; Nanda Widaninggar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to determine the total cost of production, revenue and income, and BEP of Big Chili farming per hectare in Jember Regency. Data was obtained from primary and secondary sources. Primary data was obtained from 120 farmers in Ambulu and Wuluhan Subdistricts (Big Chili farming centers in Jember Regency) by using a multistage sampling technique. Secondary data was obtained from the Agriculture Service and the Central Statistics Agency. This study uses the absolute Profit analysis and Break Event Point analysis. The results showed that big chilli farming per hectare in Jember Regency required a total production cost of Rp52.4 millions, resulting in a total revenue of Rp177.5 millions, and a net profit of Rp125.1 million. In addition, the minimum production of Big Chili farming in Jember Regency so that farmers do not experience losses is 3.771 kg per hectare. While the minimum price of Big Chili farming in Jember Regency so that farmers as not to suffer loss is Rp4.106 per kilogram.